Pre‐transplant antibody screening and anti‐CD154 costimulation blockade promote long‐term xenograft survival in a pig‐to‐primate kidney transplant model. (3rd April 2015) - Higginbotham, Laura; Mathews, Dave; Breeden, Cynthia A.; Song, Mingqing; Farris, Alton Brad; Larsen, Christian P.; Ford, Mandy L.; Lutz, Andrew J.; Tector, Matthew; Newell, Kenneth A.; Tector, A. Joseph; Adams, Andrew B.
Abstract Xenotransplantation has the potential to alleviate the organ shortage that prevents many patients with end‐stage renal disease from enjoying the benefits of kidney transplantation. Despite significant advances in other models, pig‐to‐primate kidney xenotransplantation has met limited success. Preformed anti‐pig antibodies are an important component of the xenogeneic immune response. To address this, we screened a cohort of 34 rhesus macaques for anti‐pig antibody levels. We then selected animals with both low and high titers of anti‐pig antibodies to proceed with kidney transplant from galactose‐α1, 3‐galactose knockout/CD55 transgenic pig donors. All animals received T‐cell depletion followed by maintenance therapy with costimulation blockade (either anti‐CD154 mAb or belatacept), mycophenolate mofetil, and steroid. The animal with the high titer of anti‐pig antibody rejected the kidney xenograft within the first week. Low‐titer animals treated with anti‐CD154 antibody, but not belatacept exhibited prolonged kidney xenograft survival (>133 and >126 vs. 14 and 21 days, respectively). Long‐term surviving animals treated with the anti‐CD154‐based regimen continue to have normal kidney function and preserved renal architecture without evidence of rejection on biopsies sampled at day 100. This description of the longest reported survival of pig‐to‐non‐human primate kidney xenotransplantation, now >125 days, provides promise for further study and potential clinical translation.